A mechanism-based architected material: A hierarchical approach to design Poisson's ratio and stiffness. (October 2018) - Kim, Kwangwon; Heo, Hyeonu; Ju, Jaehyung
Highlights: We demonstrated that an orthogonal and off-axis arrangement of cylindrical holes and prismatic slits of Complainant Porous Structures (CPS) enables one to build a metamaterial to have multi-stiffness and dual Poisson's ratio. We constructed a nonlinear constitutive equation of the metamaterial including contact of slit surfaces of CPS, generating a sudden increase of stiffness after the contact without changing mass density. We applied a hierarchical design approach of lattice structures to explore the effect of tessellation of CPS on the mechanical properties of metamaterials. We conducted a parametric study with geometric variables, providing a guideline for the design of CPS. Abstract: The objectives of this work is i) to synthesize a metamaterial with three-dimensional (3D) micro-architecture for variable stiffness and multiple Poisson's ratios in different directions, using cylindrical holes and slits in the 3D structural material and ii) to analyze its structural behavior. For the materials design, we use a hybrid synthesis method with Compliant Porous Structures (CPSes), producing positive and negative Poisson's ratios in the 3D space. Internal contact of slit surface of CPS under both tensile and compressive loadings is used for the variable stiffness design. We build a constitutive model of the metamaterial with CPS, verifying it with finite element (FE) based simulations and experimental tests. We apply a hierarchical design approach for lattice structures to explore the effect of tessellation of CPS on the mechanical properties of metamaterials. The spatial arrangement of cylindrical holes and slits can be used for the intelligent design of metamaterials having engineered properties, together with an edge-based hierarchical design of lattice materials. We also provide a design guideline of a cubic lattice structure on its effective properties for varying dimensions of the hybrid CPS ribs.